أنواع الفساد الواردة في سورة الشعراء: Types of Corruption Mentioned in Surat Al-Shu’araa - Alzaeem, Ibrahim; Mohd Nor, Mohd Roslan; Lokman, Ainul Asyraf (Al-Muqaddimah: Online Journal of Islamic History and Civilization, 2023)
It is not strange that the first forbidden action in the Quran is corrupting the earth. Allah says,"وَإِذَا قِيلَ لَهُمْ لَا تُفْسِدُوا فِي الْأَرْضِ قَالُوا إِنَّمَا نَحْنُ مُصْلِحُونَ" [Al-Baqarah: 11]. The verse stands as a warning from corrupting the land through corrupting other humans and messing with the norms of the universe. Corrupting people means affecting the innate nature of people with which they were created. All mankind were created with the fitra of believing in only one God, of maintaining high morals, and of refraining from low or bad habits. Allah says, "فَأَقِمْ وَجْهَكَ لِلدِّينِ حَنِيفًا ۚ فِطْرَتَ اللَّهِ الَّتِي فَطَرَ النَّاسَ عَلَيْهَا ۚ لَا تَبْدِيلَ لِخَلْقِ اللَّهِ ۚ ذَٰلِكَ الدِّينُ الْقَيِّمُ وَلَٰكِنَّ أَكْثَرَ النَّاسِ لَا يَعْلَمُونَ" [Ar-Rum: 30]. Therefore, corrupting the pure nature of people is a serious crime. The messengers, the holy books and, then, scientists are all responsible for reforming what has been corrupted, with the help of the fitra. As for the leaders, they are responsible for announcing jihad against corrupters. After a close look at surat Al-Shu’araa, the researcher found that the surah includes all types of corruption and provides a precise methodology on how to eliminate the causes of corruption and means to resist them. This study aims at identifying the types of corruption in surat Al-Shu’araa, their dangers and means of treatment. The researcher followed the analytical descriptive approach. The researcher came to the following: The Quran uses prevention as a methodology to eliminate dangers, so corruption would be warned from before happening; and the most serious type of corruption is political corruption as it affects all the institutions of the country.